Shedding of Yellow Fever Virus From an Imported Case in the Netherlands After Travel to Brazil. (13th January 2020) - Phan, My V T; Mendonca Melo, Mariana; van Nood, Els; Aron, Georgina; Kreeft-Voermans, Jolanda J C; Koopmans, Marion P G; Reusken, Chantal; GeurtsvanKessel, Corine H; Cotten, Matthew
Abstract: We report yellow fever infection in a Dutch traveler returning from Brazil. Yellow fever virus (YFV) was identified in serum and urine samples over a period of 1 month. Yellow fever virus genome sequences from the patient clustered with recent Brazilian YFV and showed with limited nucleotide changes during the resolving infection.